NEURORIGHTS FROM A MENTAL PRIVACY UPDATE - Adán Ríos, Alfredo (2023)
This article addresses the fact that neuro-rights have the potential to have a special impact on certain human rights such as privacy, freedom of thought, mental integrity, the right not to be discriminated against, the right to a fair trial or the right to Not to incriminate itself, international human rights law makes no explicit reference to neuroscience. Unlike other biomedical developments and the expert evidence in the field of neuro-law that has already been the subject of normative efforts at the national and international level, it remains largely an unknown for international human rights law. However, the implications of neuroscience and neurotechnology for inherent characteristics of human beings call for a swift and flexible response of the law in this area to mental privacy.